Activation of alpha-Fe2O3 for Photoelectrochemical Water Splitting Strongly Enhanced by Low Temperature Annealing in Low Oxygen Containing Ambient - Makimizu, Yoichi; Nguyen, Nhat Truong; Tucek, Jiri; Ahn, Hyo-Jin; Yoo, Jeong Eun; Poornajar, Mahshid; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik (Chemistry - A European Journal, 2020)
Photoelectrochemical (PEC) water splitting is a promising method for the conversion of solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (alpha-Fe2O3) is one of the most attractive materials for a highly efficient charge carrier generation and collection due to its large specific surface area and the short minority carrier diffusion length. In the present work, the PEC water splitting performance of nanostructured alpha-Fe2O3 is investigated which was prepared by anodization followed by annealing in a low oxygen ambient (0.03 % O-2 in Ar). It was found that low oxygen annealing can activate a significant PEC response of alpha-Fe2O3 even at a low temperature of 400 degrees C and provide an excellent PEC performance compared with classic air annealing. The photocurrent of the alpha-Fe2O3 annealed in the low oxygen at 1.5 V vs. RHE results as 0.5 mA cm(-2), being 20 times higher than that of annealing in air. The obtained results show that the alpha-Fe2O3 annealed in low oxygen contains beneficial defects and promotes the transport of holes; it can be attributed to the improvement of conductivity due to the introduction of suitable oxygen vacancies in the alpha-Fe2O3. Additionally, we demonstrate the photocurrent of alpha-Fe2O3 annealed in low oxygen ambient can be further enhanced by Zn-Co LDH, which is a co-catalyst of oxygen evolution reaction. This indicates low oxygen annealing generates a promising method to obtain an excellent PEC water splitting performance from alpha-Fe2O3 photoanodes.
CRIS-Team WoS Importer:2020-02-21

Activation of Osmium by the Surface Effects of Hydrogenated TiO2 Nanotube Arrays for Enhanced Hydrogen Evolution Reaction Performance - Krstajić Pajić, Mila N.; Dobrota, Ana S.; Mazare, Anca Valentina; Đurđić, Slađana; Hwang, Imgon; Skorodumova, Natalia V.; Manojlović, Dragan; Vasilić, Rastko; Pašti, Igor A.; Schmuki, Patrik; Lačnjevac, Uroš (ACS Applied Materials and Interfaces, 2023)
Efficient cathodes for the hydrogen evolution reaction (HER) in acidic water electrolysis rely on the use of expensive platinum group metals (PGMs). However, to achieve economically viable operation, both the content of PGMs must be reduced and their intrinsically strong H adsorption mitigated. Herein, we show that the surface effects of hydrogenated TiO2 nanotube (TNT) arrays can make osmium, a so far less-explored PGM, a highly active HER electrocatalyst. These defect-rich TiO2 nanostructures provide an interactive scaffold for the galvanic deposition of Os particles with modulated adsorption properties. Through systematic investigations, we identify the synthesis conditions (OsCl3 concentration/temperature/reaction time) that yield a progressive improvement in Os deposition rate and mass loading, thereby decreasing the HER overpotential. At the same time, the Os particles deposited by this procedure remain mainly sub-nanometric and entirely cover the inner tube walls. An optimally balanced Os@TNT composite prepared at 3 mM/55 °C/30 min exhibits a record low overpotential (η) of 61 mV at a current density of 100 mA cm-2, a high mass activity of 20.8 A mgOs-1 at 80 mV, and a stable performance in an acidic medium. Density functional theory calculations indicate the existence of strong interactions between the hydrogenated TiO2 surface and small Os clusters, which may weaken the Os-H* binding strength and thus boost the intrinsic HER activity of Os centers. The results presented in this study offer new directions for the fabrication of cost-effective PGM-based catalysts and a better understanding of the synergistic electronic interactions at the PGM|TiO2 interface.
CRIS-Team Scopus Importer:2023-07-21
Keywords: density functional theory; galvanic deposition; mass activity; metal-support interactions; platinum group metals

Advanced Photocatalysts: Pinning Single Atom Co-Catalysts on Titania Nanotubes - Zhou, Xin; Hwang, Imgon; Tomanec, Ondrej; Fehn, Dominik; Mazare, Anca Valentina; Zboril, Radek; Meyer, Karsten; Schmuki, Patrik (Advanced Functional Materials, 2021)
Single atom (SA) catalysis, over the last 10 years, has become a forefront in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. Most crucial when engineering a SA catalyst/support system is the creation of defined anchoring points on the support surface to stabilize reactive SA sites. Here, a so far unexplored but evidently very effective approach to trap and stabilize SAs on a broadly used photocatalyst platform is introduced. In self-organized anodic TiO2 nanotubes, a high degree of stress is incorporated in the amorphous oxide during nanotube growth. During crystallization (by thermal annealing), this leads to a high density of Ti3+-Ov surface defects that are hardly present in other common titania nanostructures (as nanoparticles). These defects are highly effective for SA iridium trapping. Thus a SA-Ir photocatalyst with a higher photocatalytic activity than for any classic co-catalyst arrangement on the semiconductive substrate is obtained. Hence, a tool for SA trapping on titania-based back-contacted platforms is provided for wide application in electrochemistry and photoelectrochemistry. Moreover, it is shown that stably trapped SAs provide virtually all photocatalytic reactivity, with turnover frequencies in the order of 4 × 106 h−1 in spite of representing only a small fraction of the initially loaded SAs.
CRIS-Team Scopus Importer:2021-06-04
Keywords: dark deposition; hydrogen generation; photocatalysis; single atom iridium; single-atom catalysis; TiO

A facile “dark”-deposition approach for Pt single‐atom trapping on facetted anatase TiO2 nanoflakes and use in photocatalytic H2 generation - Cha, Gihoon; Mazare, Anca Valentina; Hwang, Imgon; Denisov, Nikita; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdenek; Zoppellaro, Giorgio; Tesler, Alexander; Spiecker, Erdmann; Schmuki, Patrik (Electrochimica Acta, 2022)
In recent years, single-atom (SA) catalysts have become strongly investigated in electrocatalysis and increasingly also in photocatalysis. Here we demonstrate that single-crystalline anatase TiO2 nanoflake (NF) layers after a facile thermal air annealing process provide suitable anchoring sites for Pt SAs. Remarkably, such air annealed (001) faceted single-crystalline TiO2 nanoflakes can trap and stabilize Pt SAs and assemblies when immersed into a Pt precursor solution for sufficient time in absence of any illumination, i.e., under "dark deposition” conditions. These decorated species act as more efficient co-catalysts for the H2 evolution reaction, compared to the classical Pt nanoparticles (NPs). Here we show that such single-crystal-based TiO2 photocatalyst, decorated with Pt SAs, can display a 4-fold increase in photocatalytic H2 production at a lower Pt loading than observed for a classical Pt nanoparticle Pt/TiO2 arrangement.<br
Keywords: Platinum single-atom; Photocatalysis; Hydrogen generation; Single-crystal anatase TiO2; Single-atom catalysis; “Dark”-deposition

As a single atom Pd outperforms Pt as the most active co-catalyst for photocatalytic H2 evolution - Cha, Gi; Hwang, Imgon; Hejazi, Seyedsina; Dobrota, Ana S.; Pašti, Igor A.; Osuagwu, Benedict; Kim, Hyesung; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdeněk; Kment, Štěpán; Mohajernia, Shiva; et al. (iScience, 2021)
Here, we evaluate three different noble metal co-catalysts (Pd, Pt, and Au) that are present as single atoms (SAs) on the classic benchmark photocatalyst, TiO2. To trap the single atoms on the surface, we introduced controlled surface vacancies (Ti3+-Ov) on anatase TiO2 nanosheets by a thermal reduction treatment. After anchoring identical loadings of single atoms of Pd, Pt, and Au, we measure the photocatalytic H2 generation rate and compare it to the classic nanoparticle co-catalysts on the nanosheets. While nanoparticles yield the well-established the hydrogen evolution reaction activity sequence (Pt > Pd > Au), for the single atom form, Pd radically outperforms Pt and Au. Based on density functional theory (DFT), we ascribe this unusual photocatalytic co-catalyst sequence to the nature of the charge localization on the noble metal SAs embedded in the TiO2 surface.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Catalysis; Materials characterization; Nanomaterials

Black Magic in Gray Titania: Noble-Metal-Free Photocatalytic H2 Evolution from Hydrogenated Anatase - Liu, Ning; Zhou, Xuemei; Nguyen, Nhat Truong; Peters, Kristina; Zoller, Florian; Hwang, Imgon; Schneider, Christopher; Miehlich, Matthias; Freitag, Detlef; Meyer, Karsten; Fattakhova-Rohlfing, Dina; Schmuki, Patrik (Chemsuschem, 2017)
‘Black’ TiO2—in the widest sense, TiO2reduced by various treatments—has attracted tremendous scientific interest in recent years because of some outstanding properties; most remarkably in photocatalysis. While the material effects visible light absorption (the blacker, the better), black titania produced by high pressure hydrogenation was recently reported to show another highly interesting feature; noble-metal-free photocatalytic H2generation. In a systematic investigation of high-temperature hydrogen treatments of anatase nanoparticles, TEM, XRD, EPR, XPS, and photoelectrochemistry are used to characterize different degrees of surface hydrogenation, surface termination, electrical conductivity, and structural defects in the differently treated materials. The materials’ intrinsic activity for photocatalytic hydrogen evolution is coupled neither with their visible light absorption behavior nor the formation of amorphous material, but rather must be ascribed to optimized and specific defect formation (gray is better than black). This finding is further confirmed by using a mesoporous anatase matrix as a hydrogenation precursor, which, after conversion to the gray state, even further enhances the overall photocatalytic hydrogen evolution activity.
CRIS-Team Scopus Importer:2020-09-14
Keywords: absorption; hydrogen evolution; hydrogenation; photocatalysis; titania

Black TiO2 nanotubes: Efficient electrodes for triggering electric field-induced stimulation of stem cell growth - Mazare, Anca Valentina; Park, Jung Hyun; Simons, Sebastian; Mohajernia, Shiva; Hwang, Imgon; Yoo, Jeong Eun; Schneider, Christopher; Fischer, M. J.; Schmuki, Patrik (Acta Biomaterialia, 2019)
TiO2 nanostructures represent a key platform for biomedical applications, due to the combination of biocompatibility and high surface area. Especially TiO2 nanotube layers have been widely investigated due to controllable nanotopographic effects as well as for electrodes in electrostimulation experiments. In the present work we produce Ar/H2-reduced ‘black’ TiO2 nanotube arrays with a strongly enhanced electrical conductivity and explore their interaction with mesenchymal stem cells when used as electrodes to apply electric fields (EF) across the cells. While we observe no significant change in cell adhesion and their focal contact formation on these high conductivity nanotubes, we do observe a rapid stem cell response when EF is engaged using the ‘black’ TiO2 nanotube arrays as electrodes. Compared to as-formed nanotube arrays, a faster stem cell growth was observed and a lower EF intensity caused an intracellular calcium level elevation. Our results indicate that the increased conductivity in TiO2 nanotubes significantly enhances the early stem cell response to minimal electric field stimuli. Statement of Significance: The use of TiO2 nanostructures in biomedical applications is widely investigated, especially considering the nanostructured surface influence on the biomaterial-cell interactions. We have previously shown that an applied electric field (EF) on stem cells grown on TiO2 nanotubes leads to synergistic osteogenic stimulation in the absence of biochemical bone-inducing supplements. Here we report that black (i.e. highly conductive nanotubes obtained by reduction treatments) TiO2 nanotubes enable short-time EF effects on stem cells: we observe a faster stem cell growth and a significantly enhanced early stem cell response to minimal EF stimuli. The application of such nanostructures under electric field is promising for therapeutic interventions for bone regeneration and tissue engineering approaches.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Electric field; Reducing treatment; Stem cells; TiO

CdS Decorated on Hierarchically Structured Single Crystal TiO2 Nanosheets for Enhanced Photoelectrochemical H-2 Generation - Raza, Waseem; Kerketta, Ujjaval; Hwang, Imgon; Schmuki, Patrik (ChemElectroChem, 2022)
Single crystal anatase TiO2 nanosheets (TNS) were grown on a fluorine-doped tin oxide (FTO) substrate and then modified via multiple TiCl4 treatments to produce a hierarchical TiO2 structure. This high surface area hierarchical structure was then decorated with CdS (as a visible light absorber) using SILAR treatments. The resulting photoanodes provide a greatly enhanced photoelectrochemical H-2 generation capability. For the optimized TiO2 and CdS decorated TNS electrode, a photocurrent magnitude of 3.5mA/cm(2) at 0.5V Ag/AgCl (under AM 1.5G, 100mW/cm(2)) was obtained, and an applied bias to photoconversion efficiency (ABPE) of 2.5% could be reached. The increase in the specific surface was provided by the hierarchical TiO2 structure responsible for the improved performance in comparison to the plain, non-hierarchical electrode with an ABPE=0.8%. Even after particle decoration, the rapid electron flow through the single-crystalline scaffold was maintained. Consequently, the photoanode presented here best integrates in a synergistic manner, a larger surface area, a fast electron transport, and effective visible light harvesting properties.
CRIS-Team WoS Importer:2022-10-21

Critical factors for photoelectrochemical and photocatalytic H-2 evolution from gray anatase (001) nanosheets - Qin, Shanshan; Denisov, Nikita; Zhou, Xin; Zdražil, Lukáš; Fehn, Dominik; Hwang, Imgon; Bruns, Mark; Kim, Hyesung; Meyer, Karsten; Schmuki, Patrik (JPhys Energy, 2022)
In recent years, the defect engineering of titania via reduction treatments has shown a high potential for enabling efficient and co-catalyst-free photocatalytic H-2 generation from methanol/water solutions. However, defect engineering simultaneously alters several properties of TiO2. Here, we use pristine (white) and hydrogenated (gray) anatase nanosheets with dominant (001) facets. By comparing electrical conductivity, photocurrent spectra, transient photocurrent response, and photocatalytic H-2 evolution, we show that the increased conductivity or broad visible light absorption of gray titania is not responsible for its increased activity. Instead, the true bottleneck is the hole transfer rate that is significantly accelerated while using gray instead of white modification. Moreover, the hole transfer reaction causes the accumulation of the reaction products in pure water, hindering the photocatalytic H-2 evolution over time. These combined factors explain the superior performance of gray titania over white titania in photoelectrochemical or photocatalytic water splitting.
CRIS-Team WoS Importer:2022-10-07

Dye-sensitized TiO2 nanotube membranes act as a visible-light switchable diffusion gate - Hwang, Imgon; Riboni, Francesca; Gongadze, Ekaterina; Iglič, Aleš; Yoo, Jeong Eun; So, Seulgi; Mazare, Anca Valentina; Schmuki, Patrik (Nanoscale Advances, 2019)
Here we report that both-end open anodic TiO2 nanotube membranes, after sensitization with a Ru(ii)-based dye, exhibit visible-light switching properties for flow-through the nanotube channels. Under illumination, the gate is in an open state providing ∼four-times faster permeation of small molecules through the membrane compared to a dark state. Switching is reversible with no apparent dye degradation being observed. Gating is possible not only of permeating dye molecules but also of nanoprobes such as polystyrene nanospheres. Supported by quantitative modelling, we attribute the switching mechanism to light-induced changes of the charge distribution at the dye/TiO2 interface which in turn alters the hydrodynamics within the anodic tube membranes. This demonstrates that these simple dye-sensitized nanotube membranes can be used as an optically addressable flow-through gate in nanofluidics.
CRIS-Team Scopus Importer:2019-12-17

Effects of low oxygen annealing on the photoelectrochemical water splitting properties of α-Fe2O3 - Makimizu, Yoichi; Yoo, Jeong Eun; Poornajar, Mahshid; Nguyen, Nhat Truong; Ahn, Hyo-Jin; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik (Journal of Materials Chemistry A, 2020)
Photoelectrochemical (PEC) water splitting is a promising method for converting solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (α-Fe2O3) is one of the most attractive materials for highly efficient charge carrier generation and collection, due to its large specific surface area and shortened minority carrier diffusion length required to reach the surface. In the present work, PEC water splitting performance of α-Fe2O3 prepared by anodization of thin iron layers on FTO glass and subsequent annealing in a low O2-Ar atmosphere with only 0.03% O2 was investigated. The key finding is that annealing anodic nanostructures with a low oxygen concentration provides a strongly enhanced PEC performance compared with classical air annealing. The photocurrent of the former at 1.5 V vs. RHE results in 1.1 mA cm-2, being 11 times higher than that of the latter. The enhancement of the PEC performance of α-Fe2O3 annealed in a low oxygen atmosphere can be attributed to the controlled morphology, Sn doping, and introduction of oxygen vacancies, which contribute to the enhancement of the hole flux from the photogenerated site to the reactive surface and additionally lead to an enhanced hole transfer at the interface between α-Fe2O3 and the electrolyte. From the obtained results, it is evident that low oxygen annealing is a surprisingly effective method of defect engineering and optimizing α-Fe2O3 electrodes for a maximized PEC water splitting performance.
CRIS-Team Scopus Importer:2020-02-07

Fluorine Aided Stabilization of Pt Single Atoms on TiO2Nanosheets and Strongly Enhanced Photocatalytic H2Evolution - Wu, Siming; Hwang, Imgon; Osuagwu, Benedict; Will, Johannes; Wu, Zhenni; Sarma, Bidyut Bikash; Pu, Fu Fei; Wang, Li Ying; Badura, Zdenek; Zoppellaro, Giorgio; Spiecker, Erdmann; Schmuki, Patrik (ACS Catalysis, 2022)
Trapping sites in single atom (SA) catalysts are critical to the stabilization and reactivity of isolated atoms. Herein, we show that anchoring of Pt SAs on TiO2 nanosheets is strongly aided by lattice incorporated fluorine species. Tailoring the speciation of fluorine on TiO2 nanosheets is a key factor for uniform and stable dispersion of the Pt SAs and high efficiency in Pt SA co-catalyzed photocatalytic H2 production. Fluorine-stabilized uniformly dispersed Pt SAs on the (001) surface of TiO2 can provide a remarkable photocatalytic activity (a H2 production rate of 45.3 mmol h-1 mg-1 Pt for 65 mW/cm2 365 nm light). This high (maximized) efficiency can be achieved with a remarkably low loading amount of Pt SAs on TiO2 nanosheets (0.03 wt %), which is far superior to Pt nanoparticles on a TiO2 nanosheet with the same or a higher loading amount. F-stabilized Pt SAs on TiO2 nanosheets also exhibit an excellent stability in long-term photocatalytic reactions.
CRIS-Team Scopus Importer:2022-12-23
Keywords: dark deposition; photocatalysis; single atom platinum; surface fluorination; titanium dioxide

Fluorine Aided Stabilization of Pt Single Atoms on TiO2 Nanosheets and Strongly Enhanced Photocatalytic H2 Evolution - Wu, Si-Ming; Hwang, Imgon; Osuagwu, Benedict; Will, Johannes; Wu, Zhenni; Sarma, Bidyut Bikash; Pu, Fu-Fei; Wang, Li-Ying; Badura, Zdeněk; Zoppellaro, Giorgio; Spiecker, Erdmann; Schmuki, Patrik (ACS Catalysis, 2022)
Trapping sites in single atom (SA) catalysts are critical to the stabilization and reactivity of isolated atoms. Herein, we show that anchoring of Pt SAs on TiO2 nanosheets is strongly aided by lattice incorporated fluorine species. Tailoring the speciation of fluorine on TiO2 nanosheets is a key factor for uniform and stable dispersion of the Pt SAs and high efficiency in Pt SA co-catalyzed photocatalytic H2 production. Fluorine-stabilized uniformly dispersed Pt SAs on the (001) surface of TiO2 can provide a remarkable photocatalytic activity (a H2 production rate of 45.3 mmol h–1 mg–1 Pt for 65 mW/cm2 365 nm light). This high (maximized) efficiency can be achieved with a remarkably low loading amount of Pt SAs on TiO2 nanosheets (0.03 wt %), which is far superior to Pt nanoparticles on a TiO2 nanosheet with the same or a higher loading amount. F-stabilized Pt SAs on TiO2 nanosheets also exhibit an excellent stability in long-term photocatalytic reactions.<br

Hierarchical DSSC structures based on 'single walled' TiO2 nanotube arrays reach a back-side illumination solar light conversion efficiency of 8% - So, Seulgi; Hwang, Imgon; Schmuki, Patrik (Energy and Environmental Science, 2015)
In the present work we introduce a path to the controlled construction of DSSCs based on hierarchically structured single walled, self-organized TiO2 layers. In a first step we describe a simple approach to selectively remove the inner detrimental shell of anodic TiO2 nanotubes (NTs). This then allows controlled well-defined layer-by-layer decoration of these TiO2-NT walls with TiO2 nanoparticles (in contrast to conventional TiO2 nanotubes). We show that such defined multiple layered decoration can be optimized to build dye sensitized solar cells that (under back-side illumination conditions) can yield solar light conversion efficiencies to the extent of 8%. The beneficial effects observed can be ascribed to a combination of three factors: (1) improved electronic properties of the ``single walled'' tubes themselves, (2) a further improvement of the electronic properties by the defined TiCl4 treatment, and (3) a higher specific dye loading that becomes possible for the layer-by-layer decorated single walled tubes.
EAM Import::2019-03-13

Inducing a Nanotwinned Grain Structure within the TiO2 Nanotubes Provides Enhanced Electron Transport and DSSC Efficiencies >10% - So, Seulgi; Hwang, Imgon; Yoo, Jeong Eun; Mohajernia, Shiva; Mackovic, Mirza; Spiecker, Erdmann; Cha, Gi; Mazare, Anca Valentina; Schmuki, Patrik (Advanced Energy Materials, 2018)
Titania is one of the key materials used in 1D, 2D, and 3D nanostructures as electron transport media in energy conversion devices. In the present study, it is shown that the electronic properties of TiO2 nanotubes can be drastically improved by inducing a nanotwinned grain structure in the nanotube wall. This structure can be exclusively induced for “single-walled” nanotubes with a high-temperature treatment in pure oxygen atmospheres. Nanotubes with a twinned grain structure within the tube wall show a strongly enhanced conductivity and photogenerated charge transport compared to classic nano-tubes. This remarkable improvement is exempliﬁed in the electronic properties by using nanotwinned TiO2 nanotubes in dye-sensitized solar cells where a signiﬁcant increase in efﬁciency of up to 10.2% is achieved. <p
Keywords: nanotwinned; TiO2 nanotubes; conductivity; DSSCs

Inhibition of H-2 and O-2 Recombination: The Key to a Most Efficient Single-Atom Co-Catalyst for Photocatalytic H-2 Evolution from Plain Water - Hwang, Imgon; Mazare, Anca Valentina; Will, Johannes; Yokosawa, Tadahiro; Spiecker, Erdmann; Schmuki, Patrik (Advanced Functional Materials, 2022)
In the present work, it is shown that anodic TiO2 nanotubes (NTs) can be decorated with Pt, Pd, Rh, and Au single atoms (SAs) by a simple "dark deposition" approach. Such TiO2 NTs with surface trapped noble metal SAs provide a high activity for photocatalytic H-2 generation from pure water, i.e., in absence of a sacrificial agent. However, noble metals also act as active centers in the undesired hydrogen back-oxidation (H-2 + O-2 -> H2O), leading to a decrease in the overall photocatalytic H-2 production efficiency. Here it is reported that the use of noble metal co-catalysts, in the form of single atoms, can inhibit this recombination. From the different noble-metal SAs investigated, Pd SAs yield the highest H-2 production rate of 0.381 mu mol h(-1) cm(-1) at a density of 0.41 x 10(5) Pd atoms mu m(-2). Overall, the results provide a path to a highly efficient photocatalytic performance for water splitting by the suppression of the H-2/O-2 recombination, which can be effectively achieved using Pd in the form of SAs as photocatalytic co-catalysts.
CRIS-Team WoS Importer:2022-09-02

Intrinsic Cu nanoparticle decoration of TiO2 nanotubes: A platform for efficient noble metal free photocatalytic H2 production - Hejazi, Seyedsina; Mohajernia, Shiva; Wu, Yuhan; Andryskova, Pavlina; Zoppellaro, Giorgio; Hwang, Imgon; Tomanec, Ondrej; Zboril, Radek; Schmuki, Patrik (Electrochemistry Communications, 2019)
In this work, we grow intrinsically Cu-doped TiO2 nanotubes (TiNTs) by self-organizing anodization of Ti–Cu binary alloys. We demonstrate that up to a copper concentration of 1.5 at.% in the alloy, self-ordered Cu2+-doped nanotubes can be grown. Under UV illumination the Cu2+ ion-doped oxide structures can be converted to nanotubes that carry metallic nanoparticles (NPs) uniformly decorated on top of the TiNTs. We investigate the formation of these metallic nanoparticles under UV illumination by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR). The resulting intrinsic copper-doped and decorated TiNTs have a strongly enhanced photocatalytic activity for H2 evolution in comparison to pristine TiNTs. Key is the light-induced conversion of the intrinsic Cu dopant to metallic copper nanoparticles that act as a stable co-catalyst for H2 generation.
CRIS-Team Scopus Importer:2019-09-10
Keywords: Cu doped TiO; Intrinsic copper decoration; Photocatalytic activity; TiO

Li+ doped anodic TiO2 nanotubes for enhanced efficiency of Dye-sensitized solar cells - Cha, Gi; Özkan, Selda; Hwang, Imgon; Mazare, Anca Valentina; Schmuki, Patrik (Surface Science, 2022)
The insertion of cations such as H+ and Li+ to TiO2 photoelectrodes is a universally recognized method to enhance the electric conductivity of TiO2 electrodes. In the present work we report on the fabrication and use of Li+ inserted TiO2 nanotubes (NTs) as a photoanode scaffold in dye-sensitized solar cells (DSSCs). Li+ was successfully inserted into the TiO2 NTs by a cathodic treatment in 1 M LiClO4/ethylene carbonate (EC) electrolyte. We observe for DSSCs fabricated from such nanotubes an overall solar cell efficiency of ∼7.1% compared to an efficiency of ∼5.7% for the non Li-intercalated electrode. We ascribe this enhancement to a faster electron transport and an increased conductivity in the lithiated TiO2 NTs.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Anodization; Dye-sensitized solar cell (DSSC); Li ion intercalation; TiO

Li+ Pre-Insertion Leads to Formation of Solid Electrolyte Interface on TiO2 Nanotubes That Enables High-Performance Anodes for Sodium Ion Batteries - Cha, Gi; Mohajernia, Shiva; Nguyen, Nhat Truong; Mazare, Anca Valentina; Denisov, Nikita; Hwang, Imgon; Schmuki, Patrik (Advanced Energy Materials, 2019)
Recently, sodium ion batteries (SIBs) have been widely investigated as one of the most promising candidates for replacing lithium ion batteries (LIBs). For SIBs or LIBs, designing a stable and uniform solid electrolyte interphase (SEI) at the electrode–electrolyte interface is the key factor to provide high capacity, long-term cycling, and high-rate performance. In this paper, it is described how a remarkably enhanced SEI layer can be obtained on TiO2 nanotube (TiO2 NTs) arrays that allows for a strongly improved performance of sodium battery systems. Key is that a Li+ pre-insertion in TiO2 NTs can condition the SEI for Na+ replacement. SIBs constructed with Li-pre-inserted NTs deliver an exceptional Na+ cycling stability (e.g., 99.9 ± 0.1% capacity retention during 250 cycles at a current rate of 50 mA g−1) and an excellent rate capability (e.g., 132 mA h g−1 at a current rate of 1 A g−1). The key factor in this outstanding performance is that Li-pre-insertion into TiO2 NTs leads not only to an enhanced electronic conductivity in the tubes, but also expands the anatase lattice for facilitated subsequent Na+ cycling.
CRIS-Team Scopus Importer:2019-12-31
Keywords: anodization; pre-lithiation; sodium ion batteries; solid electrolyte interphases; TiO

Magnéli Phases Doped with Pt for Photocatalytic Hydrogen Evolution - Wierzbicka, Ewa; Domaschke, Maximilian; Denisov, Nikita; Fehn, Dominik; Hwang, Imgon; Kaufmann, Marlena; Kunstmann, Babette; Schmidt, Jochen; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Applied Energy Materials, 2019)
Defined TiOx suboxides (Magnéli phases) have rarely been investigated in photocatalysis. In the current work we describe a one-step synthesis of Magnéli-containing mixed phase nanoparticles that carry directly integrated minute amounts with a few hundred ppm of Pt. Nanoparticles can act as highly effective photocatalysts, e.g., mixed phase particles of 32% anatase, 11% rutile, and 57% Magnéli phases loaded with 290 ppm of Pt which provide a 50-100 times higher H2 evolution than plain anatase loaded with a similar amount of Pt. This high photocatalytic efficiency is ascribed to a multijunction of various Magnéli titania species and Pt.
CRIS-Team Scopus Importer:2019-12-20
Keywords: H; Magnéli phase; multiphase titania; photocatalysis; Pt cocatalyst

Open-Top Transparent TiO2 Nanotubes Photoanodes from Evaporated Ti Layers on Fluorine-Doped Tin Oxide - Hwang, Imgon; Schmuki, Patrik; Mazare, Anca Valentina (physica status solidi (a), 2024)
Herein, the growth of transparent TiO2 nanotube (NT) layers is investigated by complete self-organized anodization of a metallic Ti layer on fluorine-doped tin oxide glass, deposited by electron beam evaporation. An initiation-free open-top tube morphology can be obtained for such transparent TiO2 NTs using an optimized second anodization approach combined with a post-ultrasonication process. The photoelectrochemical properties of open-top tubes exhibit notable enhancement, primarily attributed to their rapid electron-transfer kinetics, with a ≈33% increase in the incident-photon-to-electron conversion efficiency value (at 350 nm wavelength) in comparison to classical (initiation-covered) NTs with a comparable morphology.
CRIS-Team Scopus Importer:2024-07-19
Keywords: anodizations; electron-transport times; initiation-free; photoelectrochemistry; transparent TiO

Optimized Polymer Electrolyte Membrane Fuel Cell Electrode Using TiO2 Nanotube Arrays with Well-Defined Spacing - Özkan, Selda; Valle, Francesco; Mazare, Anca Valentina; Hwang, Imgon; Taccardi, Nicola; Zazpe, Raul; Macak, Jan M.; Cerri, Isotta; Schmuki, Patrik (ACS Applied Nano Materials, 2020)
TiO2-based catalyst supports in polymer electrolyte membrane fuel cells (PEMFCs) are widely investigated and provide an alternative to corrosion-susceptible carbon-based catalyst supports. For PEMFCs, designing a catalyst support material with an optimal geometry is of high importance to provide high catalyst dispersion, long-term operation, and efficient fuel cell performance. In this work, we report on the use of spaced (SP) TiO2 nanotubes (NTs) as catalyst support for the cathode electrode of PEMFCs. We construct a vertically aligned Pt-TiO2 NT catalyst layer on the Nafion membrane by a threestep process: (i) growth of self-organized TiO2 nanotubes with defined intertube spacing and detachment from the Ti substrate, (ii) Pt catalyst decoration on tube walls by atomic layer deposition (ALD) or photodeposition (PD), and (iii) decal transfer of the Pt-TiO2 catalyst layer onto Nafion to fabricate a membraneelectrode assembly (MEA) by hot pressing. Such an MEA configuration based on vertically aligned high aspect ratio spaced TiO2 nanotubes with Pt catalyst decoration delivers a significantly higher fuel cell performance, compared with close-packed (CP) TiO2 nanotubes. The key for this excellent performance is that TiO2 NTs with a regular interspacing on the Nafion polymer membrane enable highly dispersed Pt catalyst decoration and provide strongly enhanced mass transport in the interspaces.
CRIS-Team WoS Importer:2020-06-19

Optimized Pt Single Atom Harvesting on TiO2 Nanotubes—Towards a Most Efficient Photocatalyst - Wu, Zhenni; Hwang, Imgon; Cha, Gi; Qin, Shanshan; Tomanec, Ondřej; Badura, Zdenek; Kment, Stepan; Zboril, Radek; Schmuki, Patrik (Small, 2021)
In the present work the authors show that anodic TiO2 nanotubes (NT) show excellent harvesting properties for Pt single atoms (Pt SAs) from highly dilute Pt solutions. The tube walls of anodic nanotubes, after adequate annealing to anatase, provide ample of suitable trapping sites—that is, surface Ti3+-Ov (Ov: oxygen vacancy) defects that are highly effective to extract and accumulate Pt in the form of SAs. A saturated (maximized) SA density can be achieved by an overnight immersion of a TiO2 NT layer to a H2PtCl6 solution with a concentration that is as low as 0.01 mm Pt. Such TiO2 NTs with surface trapped Pt SAs provide a maximized high activity for photocatalytic H2 generation (reaching a turnover frequency (TOF) of 1.24 × 106 h−1 at a density of 1.4 × 105 Pt atoms µm−2)—a higher loading with Pt nanoparticles does not further increase the photocatalytic activity. Overall, these findings show that anodic TiO2 nanotubes provide a remarkable substrate for Pt extraction and recovery from very dilute solutions that directly results in a highly efficient photocatalyst, fabricated by a simple immersion technique.
CRIS-Team Scopus Importer:2021-11-12
Keywords: dark deposition; hydrogen generation; photocatalysis; single-atom catalysis; TiO

Photoelectrochemical performance of TiO2 photoanodes: Nanotube versus nanoflake electrodes - Zhou, Xin; Denisov, Nikita; Cha, Gi; Hwang, Imgon; Schmuki, Patrik (Electrochemistry Communications, 2021)
In the present work, we compare the photoresponse of vertically erected (VE) single crystal anatase layers with that of widely used TiO2 nanotube layers. These VE-anatase layers were grown hydrothermally, directly on fluorine-doped tin oxide (FTO) glass, and consist of an array of anatase single crystal flakes with preferred (0 0 1) facets. As formed, these single crystal layers are fluorine terminated – this termination can be removed by a thermal treatment in air. We compare the photocurrent magnitude and photocurrent transients using intensity-modulated photocurrent spectroscopy (IMPS). We find that the “de-fluorinated” VE-anatase layers show significantly higher photocurrents than the comparable nanotube layers. This high efficiency of the VE-anatase layers is due to the electron transport being 100 times faster in these single crystal electrodes, provided that the blocking fluorine termination is removed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IMPS; IPCE; Photocurrent transients; TiO; VE-anatase layers

Pt Single Atoms on TiO2 Polymorphs-Minimum Loading with a Maximized Photocatalytic Efficiency - Qin, Shanshan; Denisov, Nikita; Sarma, Bidyut Bikash; Hwang, Imgon; Doronkin, Dmitry E.; Tomanec, Ondrej; Kment, Stepan; Schmuki, Patrik (Advanced Materials Interfaces, 2022)
For more than 20 years, Pt/TiO2 represents the benchmark photocatalyst/co-catalyst platform for photocatalytic hydrogen (H-2) generation. Here, single atom (SA) Pt is decorated on different polymorphs of TiO2 (anatase, rutile, and the mixed phase of P25) using a simple immersion anchoring approach. On P25 and anatase, Pt SAs act as highly effective co-catalyst for pure water splitting with a photocatalytic H-2 evolution activity (4600 mu mol h(-1) g(-1))-on both polymorphs, SA deposition yields a significantly more active photocatalyst than those decorated with classic Pt nanoparticles or conventional SA deposition approaches. On rutile, Pt SAs provide hardly any co-catalytic effect. Most remarkable, for P25, the loading of Pt SAs from precursor solution with a very low concentration (<1 ppm Pt) leads already to a maximized co-catalytic effect. This optimized efficiency is obtained at 5.3 x 10(5) atoms mu m(-2) (at macroscopic loading of 0.06 at%)-for a higher concentration of Pt (a higher density of SAs), the co-catalytic efficiency is significantly reduced due to H-2/O-2 recombination. The interactions of the SA Pt with the different polymorphs that lead to this high co-catalytic activity of SA Pt at such low concentrations are further discussed.
CRIS-Team WoS Importer:2022-07-08
Keywords: diffuse reflectance infra-red spectroscopy; photocatalytic H 2 evolution photoluminescence; Pt single atoms; TiO 2 polymorphs; X-ray absorption fine structure; X-ray absorption near-edge spectra

Self-assembled monolayers enhance the efficiency of Pt single atom co-catalysts in photocatalytic H-2 generation - Wang, Yue; Hwang, Imgon; Wu, Zhenni; Schmuki, Patrik (Electrochemistry Communications, 2021)
Single atom (SA) catalysis, over the last 10 years, has become a forefront in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. Pt SAs on titania have been reported to be a highly effective co-catalyst in photocatalytic H-2 generation. Most recently, for the synthesis of SA loading on titania surfaces, some simple immersion techniques have been described. Here we introduce a so far unexplored but evidently very effective approach to enhance the effectivity of Pt SA co-catalysts on anodic TiO2 layers. For this, we first decorate TiO2 surfaces with a partial coverage of headgroups of silane self-assembled monolayers (SAMs) and then deposit Pt SAs on this SAM modified surface. We observe a significantly enhanced photocatalytic activity for H-2 generation using this sensitization of the surface with a modified SAM.
CRIS-Team WoS Importer:2022-05-20

Single-Walled TiO2 Nanotubes: Enhanced Carrier-Transport Properties by TiCl4 Treatment - Hwang, Imgon; So, Seulgi; Mokhtar, Mohamed; Alshehri, Abdelmohsen; Al-Thabaiti, Shaeel A.; Mazare, Anca Valentina; Schmuki, Patrik (Chemistry - A European Journal, 2015)
In the present work we report significant enhancement of the photoelectrochemical properties of self- organized TiO2 nanotubes by a combined -coringof classic nanotubes followed by an appropiate TiCl4 treatment. We show that, except for the expected particle decoration, a key effect of the TiCl4 treatment is that the electron transport characteristics in TiO2 nanotubes can be drastically improved, for example, we observe an enhancement of up to 70 % in electron-transport times.
EAM Import::2019-03-13

Thermal Ramping Rate during Annealing of TiO2 Nanotubes Greatly Affects Performance of Photoanodes - Raza, Waseem; Hwang, Imgon; Denisov, Nikita; Schmuki, Patrik (physica status solidi (a), 2021)
Herein, highly ordered TiO2 nanotube (NT) arrays on a Ti substrate is synthesized in a fluoride-containing electrolyte, using the electrochemical anodization method, which yields amorphous oxide tubes. The effects of different thermal annealing profiles for the crystallization of the amorphous TiO2 NTs are studied. It is found that the temperature ramping rate has a significant impact on the magnitude of the resulting photocurrents (incident photon-to-current conversion efficiency [IPCE]) from the tubes. No appreciable changes are observed in the crystal structure and morphology of the TiO2 NTs for different annealing profiles (to a constant temperature of 450 °C). The electrochemical properties of the annealed TiO2 NTs are investigated using intensity-modulated photocurrent spectroscopy (IMPS), open-circuit potential decay, and Mott–Schottky analysis. The results clearly show that the annealing ramping rate of 1 °C s−1 leads to the highest IPCE performance. This beneficial effect can be ascribed to a most effective charge separation and electron transport (indicating the least amount of trapping states in the tubes). Therefore, the results suggest that controlling the annealing ramping rate is not only a key factor affecting the defect structure but also a powerful tool to tailor the physical properties, and photocurrent activity of TiO2 NTs.
CRIS-Team Scopus Importer:2021-05-07
Keywords: electrochemical anodization; photoanodes; photoelectrochemistry; ramping rates; TiO